Dialogue of Cultures in the Early Lyrics of the Udmurt Poet Flor Vasiliev - Victor L. Shibanov (Publishing house "Sreda", 2021)
The article is devoted to the analysis of lyrics by Flor Vasiliev (1934-1978) which is a new page in the history of Udmurt Soviet poetry. The young poet went beyond the generally accepted standards thanks to the rich literary context. This article is devoted to the study of the early lyrics of Flor Vasilyev in the aspect of the dialogue of cultures. The subject of analysis is poems written in the early 1960s. The purpose of the study is to identify and describe literary contacts with representatives of different cultures. The method of analysis is comparative studies. The result of the study is as follow: Flor Vasiliev introduces the names Remarque, Picasso, Grieg, Rembrandt into his poems to depict the general cultural atmosphere of Russia in the 1950s - 1960s, the poet follows the tradition of Russian pop lyrics. Interest in impressionism (Renoir and others) helps to hone style when portraying landscapes and the inner world of the hero. Irony begins to play a large role in the poems of early Flor Vasiliev, the poet learns in this direction from Heinrich Heine. Thus, thanks to the dialogue of cultures, there is a transition from «loud» to «quiet lyrics», humanistic traditions raise the poetry of Flor Vasiliev to a new qualitative level.